Remittances, financial development and economic growth in the economic community of West African states - Michael D. Titoe (West African Journal of Monetary and Economic Integration, 2019)
There are varied findings on how the remittances, financial development and economic growth relationship works. Some studies find that in countries with low financial development, remittance inflows may have a higher impact on economic growth by serving as a substitute for inefficient or nonexistent financial markets. Other studies show that remittance inflows enhance economic growth in countries with high financial development. This paper analyzes such tripartite relationship in the Economic Community of West African States for the period 2004-2016. Dynamic panel data estimations are carried out, and the results show that remittances positively impact economic growth while financial development is found to have no significant impact on economic growth. The interaction between the remittances and financial development variables is, however, found to have a significant, negative coefficient, implying that remittances substitute inefficient or nonexistent financial markets.
Keywords: F43; O16; 330; Remittances; Financial Development; Economic Growth